2008
DOI: 10.1007/s00464-008-9875-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic characteristics of gastric adenomas suggesting carcinomatous transformation

Abstract: The results suggest that patients with high-grade dysplasia on forceps biopsies should be considered candidates for endoscopic resection. Characteristics of gastric adenomas such as a depressed type, red color, and ulceration that may have foci of carcinomas in other parts of the adenomas also should be considered for endoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 35 publications
5
51
3
Order By: Relevance
“…Recently, Jung et al [29] reported that depressed type (OR, 4.1) and com- Characterized by an increasing architectural distortion with glandular crowding and prominent cellular atypia without stromal invasion Adenocarcinoma/carcinoma Diagnosed on nuclear and structural atypia, even when invasion is absent [45] Diagnosed when evident invasive growth of neoplastic epithelium into the lamina propria of the mucosa or beyond is observed [46] LGIN: Low-grade intraepithelial neoplasia; HGIN: High-grade intraepithelial neoplasia.…”
Section: Advantage Of Endoscopic Diagnosismentioning
confidence: 99%
“…Recently, Jung et al [29] reported that depressed type (OR, 4.1) and com- Characterized by an increasing architectural distortion with glandular crowding and prominent cellular atypia without stromal invasion Adenocarcinoma/carcinoma Diagnosed on nuclear and structural atypia, even when invasion is absent [45] Diagnosed when evident invasive growth of neoplastic epithelium into the lamina propria of the mucosa or beyond is observed [46] LGIN: Low-grade intraepithelial neoplasia; HGIN: High-grade intraepithelial neoplasia.…”
Section: Advantage Of Endoscopic Diagnosismentioning
confidence: 99%
“…In non-magnifying endoscopy, lesion size, color (red or white), macroscopic type of the lesion (depressed or others), and the presence of ulceration were examined, based on the past reports about the association between endoscopic findings and histological malignancy [6,17,20,21]. Lesion size was determined using a measuring forceps.…”
Section: Endoscopic Procedures and Diagnosismentioning
confidence: 99%
“…[4][5][6]17 In this investigation, which was based on white light endoscopic images, we found that some specimen features, including size of 15 mm or greater, depressed appearance, central concavity, and nodular surface, were useful for predicting carcinoma as a final diagnosis in FBP adenomas, regardless of histologic grades. Previous studies have suggested high-grade dysplasia as the exclusive predictive factor carcinoma as a final diagnosis, 10,11,13 though Kim et al 12 found that depressed appearance is also predictive. One large scale study of 554 cases found that high-grade dysplasia, a biopsy number of more than three, size of no less than 2.0 cm, a morphologic type of depressed or yamada type IV, and a red or mixed-orundetermined coloration were all predictive factors of carcinoma as a final diagnosis before resection.…”
Section: Discussionmentioning
confidence: 98%
“…No previous studies have found specific endoscopic findings independently predicted re-diagnosing as carcinoma after resection, with the exception of one that identified depressed-type appearance as a predictor. [10][11][12][13] Based on our experience, we hypothesize that carcinoma as a final diagnosis may be predicted in forceps biopsy- proven (FBP) adenomas based on endoscopic features such as gross appearance, color, presence of ulcerative lesions, and surface pattern (i.e., nodularity or concavity), even though inconsistent data have appeared in the literature as predictive factors of re-diagnosing as carcinoma. [10][11][12] Herein, we investigate whether these specific endoscopic findings are statistically valuable for predicting carcinoma as a final diagnosis in FBP adenomas.…”
Section: Introductionmentioning
confidence: 99%